ANALISIS KUALITAS PELAYANAN PADA KPN PRAJA NIRMALA KABUPATEN KETAPANG - Vinita Eka Putri; Achmadi Achmadi; M Basri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
Analysis of cooperative service quality is an assessment of members on the quality of cooperative services to meet the needs of members in increasing member satisfaction and loyalty. This research is in the form of an analysis of the quality of KPN services. The research approach is in the form of qualitative research and case studies. Interview respondents were members of KPN Praja Nirmala. Data collection techniques in the form of interviews, observation and documentation. The analysis of the research is interviews with 4 respondents from KPN members. The object of observation is the employee of KPN Praja Nirmala. The results of this interview and research show that the service quality of KPN Praja Nirmala is not good. The results of this study are Tangibles (not good), Reliability (good enough), Responsiveness (not good), Assurance (good enough), Empathy (not good). Tangibles weaknesses are in the form of lack of waiting chairs, administrative air conditioning, parking, reliability in the form of service time, response to members, friendliness and attention to member needs. KPN's efforts are adding waiting chairs, air conditioning, expanding parking lots, increasing service time, increasing employee response to members, friendliness and attention to members